Enzyme‐Mediated, Site‐Specific Protein Coupling Strategies for Surface‐Based Binding Assays. (31st August 2018) - Ott, Wolfgang; Durner, Ellis; Gaub, Hermann E.
Abstract: Covalent surface immobilization of proteins for binding assays is typically performed non‐specifically via lysine residues. However, receptors that either have lysines near their binding pockets, or whose presence at the sensor surface is electrostatically disfavoured, can be hard to probe. To overcome these limitations and to improve the homogeneity of surface functionalization, we adapted and optimized three different enzymatic coupling strategies (4′‐phosphopantetheinyl transferase, sortase A, and asparaginyl endopeptidase) for biolayer interferometry surface modification. All of these enzymes can be used to site‐specifically and covalently ligate proteins of interest via short recognition sequences. The enzymes function under mild conditions and thus immobilization does not affect the receptors' functionality. We successfully employed this enzymatic surface functionalization approach to study the binding kinetics of two different receptor–ligand pairs.